Pengaruh Model Pembelajaran Problembased Learning Terhadap Prestasi Belajar Mata Kuliah Askeb IV Ditinjau Dari Motivasi Belajar Mahasiswa (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Model of learning is one of the external factors, mean while the motivation is internal factors influencing learning achievement. Midwifery Mother care fourth is a difficult subject in the curriculum of the midwifery. Based on the result of the final test of students for three years, the value this subject got the lowest value among the five other subject . Model of learning is used convensional model.Objective:The purpose of this study was to determine the influence of the learning model and motivation on learning achievement of midwifery mother care fourth subjects midwifery students STIKes Karsa Husada Garut in 2013.Methods: The study design used is a randomized experimental design experiments with static group comparison. The treatment group is given the learning Problem Based Learning and the control group is given convensional model. The population in this study of all students of third semester is 85 students consisting of 2 classes. Sampling was done randomly. Data were collected by using questionnaires and achievement tests. Data analyzed by using two ways ANOVA.Result: The results of this research showed that significant there was difference among students given learning model of Problem Based Learning (PBL) and the one who was given convensional model on learning achievement, with t value = 5,835 and p value = 0.000 (p